Evolutionary tinkering of the expression of PDF1s suggests their joint effect on zinc tolerance and the response to pathogen attack - NGUYEN, Nga N. T.; RANWEZ, Vincent; VILE, Denis; SOULIE, Marie Christine; DELLAGI, Alia; EXPERT, Dominique; GOSTI, Françoise (Frontiers in Plant Science, 2014)
Multigenic families of Plant Defensin type 1 (PDF1) have been described in several species, including the model plant Arabidopsis thaliana as well as zinc tolerant and hyperaccumulator A. halleri. In A. thaliana, PDF1 transcripts (AtPDF1) accumulate in response to pathogen attack following synergic activation of ethylene/jasmonate pathways. However, in A. halleri, PDF1 transcripts (AhPDF1) are constitutively highly accumulated. Through an evolutionary approach, we investigated the possibility of A. halleri or A. thaliana species specialisation in different PDF1s in conveying zinc tolerance and/or the response to pathogen attack via activation of the jasmonate (JA) signalling pathway. The accumulation of each PDF1 from both A. halleri and A. thaliana was thus compared in response to zinc excess and MeJA application. In both species, PDF1 paralogues were barely or not at all responsive to zinc. However, regarding the PDF1 response to JA signalling activation, A. thaliana had a higher number of PDF1s responding to JA signalling activation. Remarkably, in A. thaliana, a slight but significant increase in zinc tolerance was correlated with activation of the JA signalling pathway. In addition, A. halleri was found to be more tolerant to the necrotrophic pathogen Botrytis cinerea than A. thaliana. Since PDF1s are known to be promiscuous antifungal proteins able to convey zinc tolerance, we propose, on the basis of the findings of this study, that high constitutive PDF1 transcript accumulation in A. halleri is a potential way to skip the JA signalling activation step required to increase the PDF1 transcript level in the A. thaliana model species. This could ultimately represent an adaptive evolutionary process that would promote a PDF1 joint effect on both zinc tolerance and the response to pathogens in the A. halleri extremophile species.